Prevalence of lumbar spondylosis and its association with low back pain among community-dwelling Japanese women. Issue 1 (December 2016) - Tsujimoto, Ritsu; Abe, Yasuyo; Arima, Kazuhiko; Nishimura, Takayuki; Tomita, Masato; Yonekura, Akihiko; Miyamoto, Takashi; Matsubayashi, Shohei; Tanaka, Natsumi; Aoyagi, Kiyoshi; Osaki, Makoto
Abstract Background Lumbar spondylosis is more prevalent among the middle-aged and elderly, but few population-based studies have been conducted, especially in Japan. The purpose of this study was to explore the prevalence of lumbar spondylosis and its associations with low back pain among community-dwelling Japanese women. Methods Lateral radiographs of the lumbar spine were obtained from 490 Japanese women ≥ 40 years old, and scored for lumbar spondylosis using the Kellgren-Lawrence (KL) grade at lumbar intervertebral level from L1/2 to L5/S1. Height and weight were measured, and body mass index (BMI) was calculated. Low back pain in subjects was assessed using a self-administered questionnaire. Stiffness index (bone mass) was measured at the calcaneal bone using quantitative ultrasound. Results Prevalence of radiographic lumbar spondylosis for KL ≥ 2, KL ≥ 3 and low back pain were 76.7%, 38.8% and 20.0%, respectively. Age was positively associated with radiographic lumbar spondylosis (KL = 2, KL ≥ 3) and low back pain. Greater BMI was associated with lumbar spondylosis with KL = 2, but not with KL ≥ 3. Stiffness index was associated with neither radiographic lumbar spondylosis nor low back pain. Multiple logistic regression analysis identified radiographic lumbar spondylosis (KL ≥ 3) at L3/4, L4/5 and L5/S1 was associated with low back pain, independent of age, BMI and stiffness index. Conclusion Severe lumbar spondylosis at the middle or lower level may contribute to low back pain.